The Influence of Employee Empowerment, Career Opportunities, and Job Satisfaction on Organizational Performance in Medium-Sized Companies in West Java - Amalia, Mei Rani; Najmudin, Najmudin; Sudarto, Sudarto; Anggraeni, Ade Irma (Eastasouth Institute, 2025)
This study investigates the impact of employee empowerment, career opportunities, and job satisfaction on organizational performance in medium-sized companies in West Java. A quantitative approach was employed, with data collected from 350 respondents using a Likert scale (1-5) and analyzed through Structural Equation Modeling-Partial Least Squares (SEM-PLS). The findings reveal that employee empowerment and career opportunities significantly and positively influence organizational performance. Job satisfaction also mediates these relationships, amplifying their effects. The study underscores the importance of fostering empowerment, providing structured career development opportunities, and enhancing job satisfaction to achieve superior organizational outcomes. Practical implications suggest that medium-sized companies should adopt employee-centric strategies to enhance performance and maintain competitiveness.